Podzamcze in Lublin – spatial development and opinion on the building Nadstawna 2-4 - Borowski, Łukasz; Skoczylas, Olga; Nepelski, Krzysztof (Budownictwo i Architektura / Civil and Architectural Engineering, 2016)
This article discusses the future of the premise located at 2-4 Nadstawna in Lublin. The reasons behind this publication are not only changes to the purpose of the building in question implemented in the Local Zoning Plan (5.2015) for Podzamcze but also its poor technical condition. This means that the property will not be used for commercial and office-related purposes but, instead, it will be aimed at residential and servicerelated ones. The new owner of the discussed premises (since 02.2015) will therefore need to decide whether to renovate the existing building and omit to change its current function or to erect a new property in compliance with the local zoning plan being in force at present. The authors of this article are of the opinion that this decision will be of considerable importance for developing the space in this part of the city. For the purposes of this publication, Borowski, Skoczylas, and Nepelski analysed the technical condition of the property, investment funds to be allocated, optimal development of the building, modernisation and extension plans, as well as the influence that the property may exert on the surrounding area. Furthermore, the reasons and results of building subsidence were also investigated.